Systematic significance of bulb morphology of the Southern African members of Oxalis L. (Oxalidaceae) - Gebregziabher, Awot Kiflu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.